Penguatan Efikasi Diri Pedagang Pasar Tradisional Melalui Pelatihan Kewirausahaan yang Berorientasi pada Modal Psikologi Positif - Elpisah Amir; Muhammad Hasan (DEDIKASI, 2019)
Entrepreneurship development programs must not only be carried out in formal education, such as at the level of primary, secondary and tertiary education, but also must be developed in informal and non-formal education in the community. The entrepreneurship program also has to be applied for traditional market traders. The training activity aims to provide an understanding of the importance of positive psychological capital in the management and sustainability of businesses for the traditional market traders. The training activity was conducted at the Laboratory of Economic Education Study Program, Faculty of Economics, Makassar State University, which was attended by traditional market traders from 3 traditional markets in Makassar City. The implementation of this activity strongly supports the entrepreneurship program in the informal sector. Because by doing this program, it can provide added value for traditional market traders in managing the sustainability of their business. There were changes of knowledge and attitudes of traditional market traders after participating in this activity. It could be seen from the increase of the participants' post-test score compared to the pre-test score.